ANALISIS ANALISIS PEMASARAN USAHA TAMBAK UDANG WINDU DAN UDANG VANAME DI DESA SEPATIN KECAMATAN ANGGANA KABUPATEN KUTAI KARTANEGARA - Takbir, Mashudan; Fahrizal, Wahyu; Oktawati, Nurul Ovia (Pena Akuatika : Jurnal Ilmiah Perikanan dan Kelautan, 2025)
This study aims to analyze marketing channels, marketing margins, shrimp farmer's share, marketing costs, profit-to-cost ratio, and marketing efficiency for black tiger shrimp (Penaeus monodon) and vaname shrimp (Litopenaeus vannamei) in Sepatin Village, Anggana District, Kutai Kartanegara Regency. The sampling method used purposive sampling and snowball sampling, involving 40 farmer respondents and 2 marketing institutions. The results show two marketing channel patterns: one-level channels (Producer-Collector-End Trader) and two-level channels (Producer-Collector-Retailer-Consumer). The marketing margins for black tiger shrimp and vaname shrimp in the level one channel were Rp 4,600/kg and Rp 6,500/kg, respectively, while the level two channel reached Rp 10,000/kg. The shrimp farmer's share for level one was 97% for black tiger shrimp and 92% for vaname shrimp, whereas level two was only 2%. Marketing efficiency for level one ranged from 1% to 2%, while level two reached 3% and 38,7%. These findings demonstrate that the level one marketing channel is more efficient than level two. Keywords: Marketing Channel, Marketing Margin, Marketing Efficiency of Tiger Shrimp and Vaname Shrimp.